The Effects of Extractives Substances for Bonding Performance of Three Natural Binder on Nipa Fronds Particleboard - Santoso, M; Widyorini, R; Agus Prayitno, T; Sulistyo, J (KnE Life Sciences, 2019)
Nipa (Nypa Fruticans Wurmb) is a non-wood material that potential as a raw material of the composite board. One of the disadvantages of the nipa fronds is it contains very high extractives and inorganic substances. The presence of high content of extractives in raw material of particleboard potentially be an obstacle in the process of gluing the composite board. The existing of extractive substances on the surface of the composite board raw materials contributes to make the bonding process is not going well. On the other side, the utilization of natural binder for non–wood composite is still limited. Maltodextrin, sucrose, and citric acid is a potential natural binding agent for composite products. This research focused to investigate the effects of extractive substances for bonding performance of three natural binders (maltodextrin, sucrose, and citric acid) for nipa fronds particleboard. The particles screened passed through aperture sizes of 10 mesh and treated with three condition (un–extraction, hot water extraction, and n–hexane extraction) were used as materials in this research. The addition of natural binder of 10 % air dried particles was done and pressing temperature was set at 180 ∘C under a pressure of 3.6 MPa during 10 min. Physical and mechanical properties were done according to JIS A 5908 : 2003. The most optimum particleboards on this research was a citric acid bonded particleboard with hot water extraction which produces particleboard with characteristics i.e. density 0.84 g · cm−3, moisture content 7.44 %; thickness swelling 1.12 %; water absorption 21.83 %; surface roughness 7.57 μm; internal bonding strength 0.49 MPa; modulus of rupture 10.42 MPa, and modulus of elasticity 3.65 GPa. All of the properties meet the 5908 : 2003. Keywords: Citric acid, Extractives substance, Maltodextrin, Nipa frond, Particleboard, Sucrose